Numerical Studies on the Oil-Water Mixture Separation by Corrugated Plates with Hooks and Holes in Various Shapes and Configurations - Oruc, Mehmet; Salih, Muhammed; Yayla, Sedat; Bayraktar, Seyfettin (SPRINGER HEIDELBERG, 2025)
The present paper reports the studies on the separation efficiency of a water-oil mixture in the second process in which the water consists of 5-10% crude oil in general. The mixture in this stage was exposed to an additional separation. For this purpose, corrugated plates with L-shaped hooks and holes on the top intersection of the plates were used. Before handling some design factors such as the hole pattern at the intersection of the inclined plates, the inclination angle of the corrugated plates, and the hooks attached to the plates, an experimental rig was designed to validate the computational fluid dynamics (CFD) results. Upon achieving a successful comparison, the numerical studies were extended to reveal the effects of hole shapes and arrangement pattern and the angle of the plates. It was found that attaching L-shaped hooks to the plates improves separation effectiveness by 2% as compared to hookless plates. The parametric CFD studies reveal that the hole shapes do not affect considerably the separation efficiency while raising the plates increases the efficiency slightly and pressure drop dramatically.
Keywords: Separation; Computational fluid dynamics (CFD); Laminar flow; WASTE-WATER; FLOW; PERFORMANCE; MODEL; GAS; Science & Technology - Other Topics